Neovascularization in Human Intracranial Atherosclerotic In-Stent Restenosis - Yiding Feng; Adam A. Dmytriw; Bin Yang; Liqun Jiao (Diagnostics, 2021)
Optical coherence tomography (OCT) has seen widespread use in cardiovascular and interventional endovascular imaging. While scattered reports of intracranial usage have been reported for the assessment of atherosclerotic stenosis, nutrifying neovasculature supplying plaque and neointima have not been demonstrated until now. We report the first in-vivo illustration of this phenomenon, which is a high-resolution depiction of a critical pathway for in-stent restenosis.